A Late Holocene environmental history of a bat guano deposit from Romania: an isotopic, pollen and microcharcoal study. (1st November 2015) - Forray, Ferenc L.; Onac, Bogdan P.; Tanţău, Ioan; Wynn, Jonathan G.; Tămaş, Tudor; Coroiu, Ioan; Giurgiu, Alexandra M.
Abstract: A 1.5-m-long core from a bat guano deposit in Zidită Cave (western Romania) has provided a 900-year record of environmental change. Shifts in δ 13 C values of bulk guano (between −22.6 and −27.5‰) combined with guano-sourced pollen and microcharcoal information show significant changes in the structure of vegetation and plant biomass. Cave guano δ 13 C values reflect the dietary preferences of bats which are controlled by local vegetation dynamics, which in turn depend on local climatic conditions. Neither δ 13 C values nor pollen association in guano changed strikingly over the Medieval Warm Period (MWP) and Little Ice Age (LIA) transition. Instead, an overall decreasing trend of δ 13 C values between ca. AD 1200 and 1870–1900 defines the duration of LIA. A shift toward cooler and wetter conditions at ca. AD 1500 noticed in the pollen record by an increase in Fagus sylvatica and Alnus and the decrease of Carpinus betulus, may indicate the first major change at the beginning of the LIA. Evidence for two major cold spells occurring around AD 1500 and ca. AD 1870 comes from both δ 13 C and pollen record. In between these events, the cave region experienced a warmer and drier climate but colder and wetter than the MWP, favouring the expansion of Quercus, Fraxinus and Tilia simultaneously with the decrease of F. sylvatica and Poaceae. Human impact in the studied area is mainly related to agriculture, grazing and deforestation. The effects are most pronounced after AD 1845 when the pollen of cereals increases and Zea is recorded (AD 1845). Higher percentages of microcharcoal particles in the guano sequence are generally correlated with agricultural activities like land cleaning via controlled fires. Graphical abstract: Highlights: Late Holocene high resolution, multi-proxy records from a bat guano deposit in western Romania. Hydroclimate changes inferred from δ 13 C of bulk guano and pollen assemblage. MWP/LIA transition was less dramatic compare to the demise of LIA. LIA is bracket between two major cold spells occurring around AD 1500 and ca. AD 1870 Human impact in the studied area is mainly related to agriculture, grazing and deforestation.